The Effect of Disruptive Factors on Inventory Control as a Mediator and Organizational Performance in Health Department of Punjab, Pakistan - Hashmi, Aamir Rashid; Mohd, Adnan Tawfiq (International Journal of Sustainable Development & World Policy, 2020)
The organizational performance at Punjab healthcare is crucial and often faces stock-outs of critical medicines and equipment at the emergency department of different hospitals, which increased the mortality rate. Therefore, the study determined the effect of disruptive factors and inventory control as a mediator on organizational performance. The quantitative method with survey questionnaires on a 200 sample size through cluster sampling was used. SPSS and AMOS were used to examine Exploratory Factor Analysis, Confirmatory Factor Analysis, and Structural Equation Modeling. The results found full mediation with a significant positive effect between study variables. The finding indicated that the strict compliance of standardized operating procedures, professionally well-equipped staff, stock availability, and accurate inventories could reduce costs with improved service quality. This study is useful to the public healthcare facilities, ministries managing inventories, and to the body of knowledge. Finally, the back-log inventories at public sector organizations need to be researched in the future.